Shear Bond Strength of Self-Adhesive Flowable Composite, Conventional Flowable Composite and Resin-Modified Glass Ionomer Cement to Primary Dentin - Kiana Poorzandpoush; Mehdi Shahrabi; Alireza Heidari; Zohre Sadat Hosseinipour (Tehran University of Medical Sciences, 2019)
Objectives: This study aimed to compare the shear bond strength (SBS) of self-adhesive and conventional flowable composites and resin-modified glass-ionomer cement (RMGIC) to primary dentin. Materials and Methods: In this in vitro, experimental study, the buccal surface of 48 primary canine and first molar teeth was longitudinally sectioned to expose dentin. The teeth were randomly divided into three groups (n=16) of 37.5% phosphoric acid+ OptiBond+ Premise Flow composite (group 1), Vertise Flow composite (group 2) and RMGIC (group 3). A plastic cylindrical mold was placed on the exposed dentin and filled with restorative materials. The samples were then immersed in distilled water at 37°C for 24 hours, subjected to 1000 thermal cycles between 5-55°C and underwent SBS test. The mode of failure was determined under a stereomicroscope. Data were analyzed using one-way ANOVA and Tukey's test. Results: A significant difference was noted in SBS of the groups (P<0.05). The SBS of conventional flowable composite was significantly higher that of RMGIC and self-adhesive flowable composite (P<0.05). The difference in SBS of RMGIC and self-adhesive flowable composite was not significant (P>0.05). Failure at the dentin-restoration interface (adhesive failure) had the highest frequency in groups 1 and 2. The frequency of adhesive failure was 100% in group 3. Conclusions: Within the limitations of this study, the conventional flowable composite yielded the highest SBS to primary dentin. Self-adhesive flowable composite and RMGIC showed the lowest SBS with no significant difference with each other.